Kebijakan Penataan dan Pengelolaan Parkir Sebagai Upaya Peningkatan Pendapatan Asli Daerah - asmarudin, imam; Sugiharto, Imawan; Riyanti, Ratna; Abdurrachman, Hamidah (Universitas Pancasakti Tegal, 2020)
The purpose of this research is to explore how the potential of local native income from the sector of structuring the management of expertise in Tegal Regency. Taxes and levies are one of the sources of local income that can be returned to the community as a form of welfare, the form of return from local government are to provide good public services, orderly, safe and comfortable, one of which is in parking, management and arrangement of parking is a business that has income value. This research uses an empirical juridical approach where primary data is the main data, data obtained through observation and interview, then data processed descriptively analytically. Retribution is one of the sources of revenue Tegal regency should be selectively optimized. The arrangement of parking, management is expected to increase the income of the area as the original income of the region and vice versa for the community to feel its benefits, comfort, order, and security in parking. Based on data in 2020 Tegal district government has a total parking location point of 269 with parkers as many as 412 people, if the levy is carried out correctly and by the nominal deposited estimated Local Native Income from the parking management sector reaches Rp. 697,488,000,000. Seeing this potential requires policy breakthroughs for local governments in managing to park, one of which is by making Local Regulations on Parking Arrangement and Management